Hematopoietic Stem Cell Transplantation in the Leukodystrophies: A Systematic Review of the Literature - Musolino, Patricia L.; Lund, Troy C.; Pan, Jessica; Escolar, Maria L.; Paker, Asif M.; Duncan, Christine N.; Eichler, Florian S. (Neuropediatrics, 2014)
Objective The objective of this study is to systematically review the literature on worldwide numbers of leukodystrophy patients undergoing hematopoietic stem cell transplantation (HSCT) as well as the safety and efficacy of the procedure in this patient population.Materials and Methods A PubMed and EMBASE search up to June 2012 was conducted with a manual search of references from relevant articles. Selected studies were evaluated using internationally accepted criteria. The effect estimates of HSCT upon survival in early-stage disease versus late-stage disease were compared.Results One hundred and fifty-two studies qualified for inclusion and reported on a total of 689 patients. Study quality ranged from poor to good; no study was rated excellent. Small sample sizes limited most studies. Meta-analysis in a subset of larger studies indicates that transplantation in earlier stages of disease fairs better than in the late stages. Beyond survival, little longitudinal data on functional outcome is reported and neurological outcome is sparse.Conclusion Further studies are needed to determine the neurological outcome following HSCT in the leukodystrophies. HSCT in the early stages of cerebral disease is still recommended for select leukodystrophies.
Keywords: leukodystrophy; bone marrow transplantation; white matter diseases